Inspiratory muscle strength and six-minute walking distance in heart failure : prognostic utility in a 10 years follow up cohort study - Ramalho, Sergio Henrique Rodolpho (2019)
Background Maximal inspiratory pressure (PImax) and 6-minutes walk distance test (6MWD) may be more available and feasible alternatives for prognostic assessment than cardiopulmonary testing. We hypothesized that the PImax and 6MWD combination could improve their individual accuracy as risk predictors. We aimed to evaluate PImax ability as a mortality predictor in HF and whether the combination to 6MWD could improve risk stratification. Methods Prospective cohort from HF Clinics of three University Hospitals. PImax, 6MWD and pVO2 were obtained at baseline. The end point was all cause mortality. Results Consecutive 256 individuals (50% woman, 57.4±10.4years) with low ejection fraction (LVEF) (31.8±8.6%) were followed up to 10years. During a median follow-up of 34.7 (IQR 37) months, 110 participants died. Mean±SD values were: pVO2 14.9±5.1mL/kg/min, PImax 5.5±1.3kPa and 6MWD 372±118m. In multivariate Cox regression, pVO2, PImax, 6MWD and LVEF were independent mortality predictors. The pVO2 showed gold standard accuracy, followed by PImax (AUC = 0.84) and 6MWD (AUC = 0.74). Kaplan-Meier mean survival time (MST±SE) for lower (≤5.0kPa) and higher (>6.0kPa) PImax tertiles, were 37.9±2.8months and 105.0±5.2months respectively, and addition of 6MWD did not restratified risk. For intermediate PImax tertile, MST was 81.5±5.5months, but adding 6MWD, MST was lower (53.3±7.6months) if distance was ≤350m and higher (103.1±5.7months) for longer distances. Conclusion PImax is an independent mortality predictor in HF, more accurate than 6MWD and LVEF. Addition of 6MWD empowers risk stratification only for intermediate PImax tertile. Although less accurate than pVO2, this simpler approach could be a feasible alternative as a prognostic assessment.